EFFICACY OF SEED TREATMENT WITH BIJAMRITA AND BAVISTIN ON SEEDLING GROWTH OF CUCURBITS AND LEGUMES - B. K. JHA; OMKAR KUMAR.; S. K. NAIK.; PRADIP KUMAR SARKAR; J. S. CHOUDHARY; RESHMA SHINDE (The Bioscan, 2021)
A detailed study on seed treatments with bijamrita and bavistin on cucurbits and legumes were undertaken. The bijamrita treated seeds in cucurbits and legumes showed highest germination in bitter gourd (92.5%) and vegetable soybean (84%). The bitter gourd, bottle gourd and cucumber showed significantly highest shoot length (14.45, 17.35 and 22.90 cm), root length (13.35, 10.03 and 12.10 cm) and seedling length (27.80, 27.40 and 34.35 cm) in comparison to bavistin. In leguminous black gram, cow pea and vegetable soybean treated with bijamrita showed highest shoot length (14.93, 24.38 and 25.77 cm), root length (8.10, 14.98 and 16.10 cm) and seedling length (23.02, 39.35 and 40.00 cm). Similarly, highest root volume (2.56, 4.45 and 2.20 cc), fresh weight (6.17, 14.18 and 6.07 g) and seed vigour index (2570, 2536 and 3022) recorded in bitter gourd, bottle gourd and cucumber. Similarly highest root volume (1.30, 2.56 and 6.70 cc); fresh weight (1.83, 8.56 and 7.60 g) and seed vigour index (1884, 2838 and 3525) in bijamrita treated seeds of black gram, cow pea and vegetable soybean. Seed treated with bijamrita in cucurbits and legumes has significant effect on seed germination and seedling growth which promote eco-friendly agriculture devoid of chemicals.